Lentes de contacto y su efecto en la calidad visual de los pacientes que acuden a la iglesia del Evangelio Cuadrangular “La Alborada”. Guayaquil. Noviembre 2023 -abril 2024. - Cedeño Delgado, Rebeca Judith (2024)
The research project examined the effect of contact lenses on the visual quality of young patients attending the Foursquare Gospel Church "La Alborada" in Guayaquil, between November 2023 and April 2024. Specific objectives were set to define the subjective perception of visual quality, analyze the comfort and satisfaction with the use of contact lenses, and identify possible side effects. The methodology used was deductive and analytical, with a quantitative approach. The findings revealed that more than 50% of the young people presented a visual acuity of 20/20 with the correction provided by contact lenses. However, some participants showed low tear production, which could rule out their suitability for contact lens wear. In addition, significant improvements in participants' visual acuity were observed, although some young people with astigmatism experienced difficulties in lens fitting. The research contributes to the understanding of how contact lenses can improve visual quality, highlighting their beneficial effect on visual acuity and visual field in young patients. These findings underscore the importance of proper contact lens wear and provide information relevant to ophthalmic practice and the visual well-being of the community studied.